The impact of the Atmosphere on space-bound Vehicles - Perimeter Institute (Perimeter Institute, 2013)
When rockets and space-bound vehicles are fired into space, they have to deal
with turbulence, winds and waves in the Earth's atmosphere. Different height
regimes cause different problems. In the lower regions (0 to 20 km altitude),
winds and turbulence are major issues, whereas above 50 km altitude, large
atmospheric waves have serious importance on safe passage. Similar issues arise
on re-entry. In this talk, I will discuss the ways in which these atmospheric
phenomena manifest themselves, and how they are best mitigated. One example of
particular significance will be the Space Shuttle Columbia disaster, for which I
consulted with NASA in respect to possible atmospheric influences. I will also
describe some of the instrumentation used to measure these phenomena.